Zebrafish biosensor for toxicant induced muscle hyperactivity - Shahid, Maryam; Middel, Volker; Strähle, Uwe (Scientific reports, 2016)
Robust and sensitive detection systems are a crucial asset for risk management of chemicals, which are produced in increasing number and diversity. To establish an in vivo biosensor system with quantitative readout for potential toxicant effects on motor function, we generated a transgenic zebrafish line TgBAC(hspb11:GFP) which expresses a GFP reporter under the control of regulatory elements of the small heat shock protein hspb11. Spatiotemporal hspb11 transgene expression in the musculature and the notochord matched closely that of endogenous hspb11 expression. Exposure to substances that interfere with motor function induced a dose-dependent increase of GFP intensity beginning at sub-micromolar concentrations, while washout of the chemicals reduced the level of hspb11 transgene expression. Simultaneously, these toxicants induced muscle hyperactivity with increased calcium spike height and frequency. The hspb11 transgene up-regulation induced by either chemicals or heat shock was eliminated after co-application of the anaesthetic MS-222. TgBAC(hspb11:GFP) zebrafish embryos provide a quantitative measure of muscle hyperactivity and represent a robust whole organism system for detecting chemicals that affect motor function.